2015
DOI: 10.5830/cvja-2015-055
|View full text |Cite
|
Sign up to set email alerts
|

Lack of cardioprotection by single-dose magnesium prophylaxis on isoprenaline-induced myocardial infarction in adult Wistar rats

Abstract: SummaryAimMagnesium (Mg2+) is effective in treating cardiovascular disorders such as arrhythmias and pre-eclampsia, but its role during myocardial infarction (MI) remains uncertain. In this study, we investigated the effects of Mg2+ pre-treatment on isoprenaline (ISO)-induced MI in vivo.MethodsRats divided into four groups were each pre-treated with either MgSO4 (270 mg/kg intraperitoneally) or an equivalent volume of physiological saline, prior to the ISO (67 mg/kg subcutaneously) or saline treatments. One da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Oxidative stress has been considered a conjoint pathological mechanism, and it contributes to initiation and progression of various cardiovascular dysfunctions, such as myocardial infarction (MI) [30,31]. Moreover, many researchers have suggested that oxidative stress induces amplification of the inflammatory response and apoptosis leading to the initiation of ischemic lesion [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been considered a conjoint pathological mechanism, and it contributes to initiation and progression of various cardiovascular dysfunctions, such as myocardial infarction (MI) [30,31]. Moreover, many researchers have suggested that oxidative stress induces amplification of the inflammatory response and apoptosis leading to the initiation of ischemic lesion [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…When used in excessive doses, isoproterenol exerts deleterious effects on the heart of myocardial infarction model rats, leading to many morphological, pathophysiological, and metabolic aberrations comparable to those taking place in human MI. [4][5][6][7] Since MI remains a public health problem resulting in morbidities and mortalities at higher rates, 8 several studies have been focused, over the last few years, on the development of new synthetic compounds with promising pharmacological activity for prevention and treatment of MI or cardiovascular diseases. [9][10][11] Coumarins, acting as antagonists to vitamin K, are widespread natural chemicals found in a variety of plant sources that represent the most promising cardioprotective compounds playing an important role against thromboembolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Since MI remains a public health problem resulting in morbidities and mortalities at higher rates, 8 several studies have been focused, over the last few years, on the development of new synthetic compounds with promising pharmacological activity for prevention and treatment of MI or cardiovascular diseases 9–11 . Coumarins, acting as antagonists to vitamin K, are widespread natural chemicals found in a variety of plant sources that represent the most promising cardioprotective compounds playing an important role against thromboembolic diseases 12 .…”
Section: Introductionmentioning
confidence: 99%
“…MI is characterized by an acute condition of ischemic necrosis of heart muscle that occurs as a result of the interruption in the supply of myocardial oxygen and nutrients ( Zhou et al, 2008 ). Overstimulation of isoproterenol (ISO), a synthetic β-adrenergic receptor agonist was reported to induce MI through severe cardiac stress, including the highly cytotoxic free radicals producing, intracellular Ca 2+ overload, and apoptosis ( Garson et al, 2015 ). The experimental model of ISO-induced MI offered a reliable technique to investigate the efficacy of various potentially cardioprotective agents, which has been frequently documented in previous studies ( Fathiazad et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%